DEVELOPMENT OF AUGMENTED REALITY BOOK-BASED LEARNING MEDIA ON THE LIFE CYCLE OF LIVING ORGANISMS TO ENHANCE CREATIVE THINKING SKILLS OF THIRD-GRADE ELEMENTARY STUDENTS - Putra, I Putu Eka Permana; Artini, Ni Putu Juni; Dharma, I Made Aditya (STKIP Citra Bakti, 2026)
Elementary education serves as the foundational stage for developing students’ creative thinking skills. However, these skills often do not reach their full potential, largely due to the continued reliance on traditional teaching and the limited application of innovative instructional media. This challenge is particularly evident in teaching the topic of the life cycles of living organisms, which tends to be abstract and difficult for third-grade students to grasp. This research focused on developing an Augmented Reality (AR) Book to serve as a learning resource and to evaluate its validity, ease of use, and effectiveness in promoting students’ creative thinking skills. This research adopted a Research and Development (R&D) method with the ADDIE model serving as its development framework. The model is organized into five main stages: analysis, design, development, implementation, and evaluation. Participants included third-grade students, their teachers, as well as specialists in both subject matter and educational media. Information was collected using interviews, surveys, and testing, and was subsequently analyzed to assess the learning medium’s credibility, practical application, and overall effectiveness in enhancing students’ capacity for creative thought. The analysis results indicate that the Augmented Reality Book has high validity, is easy to implement in the classroom, and effectively enhances students’ creative thinking skills. The use of interactive features and three-dimensional visualizations enables students to understand concepts more concretely and with greater engagement. In conclusion, this learning medium is suitable as an instructional innovation and provides important implications for improving the quality of elementary education by making learning more interactive, engaging, and meaningful.